The neurohormone tyramine stimulates the secretion of an insulin-like peptide from the Caenorhabditis elegans intestine to modulate the systemic stress response - Veuthey, Tania Vanesa (2025)
The DAF-2/insulin/insulin-like growth factor signaling (IIS) pathway plays an evolutionarily conserved role in regulating reproductive development, life span, and stress resistance. In Caenorhabditis elegans, DAF-2/IIS signaling is modulated by an extensive array of insulin-like peptides (ILPs) with diverse spatial and temporal expression patterns. How- ever, the release dynamics and specific functions of these ILPs in adapting to different environmental conditions remain poorly understood. Here, we show that the ILP, insulin-3 (INS-3), plays a crucial role in modulating the response to various environmental stress- ors in C. elegans. ins-3 mutants display increased resistance to heat, oxidative stress, and starvation; however, this advantage is countered by slower reproductive development under favorable conditions. We find that ins-3 expression is downregulated in response to environmental stressors, whereas, the neurohormone tyramine, which is released during the acute flight response, increases ins-3 expression. We show that tyramine induces intestinal calcium (Ca2+) transients through the activation of the TYRA-3 receptor. Our data support a model in which tyramine negatively impacts environmental stress resistance by stimulating the release of INS-3 from the intestine via the activation of a TYRA-3-Gαq-IP3 pathway. The release of INS-3 systemically activates the DAF-2 pathway, resulting in the inhibition of cytoprotective mechanisms mediated by DAF-16/FOXO. These studies offer mechanistic insights into a brain–gut communication pathway that weighs adaptive strate- gies to respond to acute and long-term stressors.